Development of State Green Sukuk as A Government Effort to Realize Green Environment - Yulitasari, Lis; Tresiana, Novita; Ekawati, Evi (Universitas Trunojoyo Madura, 2023)
Along continued issue development of green and sustainable development, fundraised for finance project greening keep going increase. Principle invests in Islamic finance combined with a draft-friendly environment and sustainability. The instrument of innovative Islamic finance-based continuity, like Green Sukuk in Indonesia, offers potential and importance for supporting the development economy in line with the effort protection environment. This study aims to know the development of green sovereign Sukuk as part of creative and innovative financial market financing Islamic (financing development).The method used by the author is qualitative, with a review of the literature. Literature research is a way to find relevant references to problems that arise.Research results show that the issuance of green Sukuk is an effort application sustainability in Indonesia. Green Sukuk is significant in Indonesia because this country is one of the countries with a level of vulnerability and high disaster. Disaster frequently happens in Indonesia. Tragedy growing hydrometeorology increase consequence change, and increasing climate increase consequence development sustainability, which is not noticed environment. The more many developments continuously neglect the environment and influence change climate with the way it cause droughts and floods, which then influence the economy.